Quality of Care in Psychosis and Bipolar Disorder From the Service User Perspective. (December 2013) - Skelly, Niamh; Schnittger, Rebecca I.; Butterly, Lisa; Frorath, Charlotte; Morgan, Craig; McLoughlin, Declan M.; Fearon, Paul
According to the recovery model of mental health care, service development should incorporate the expert knowledge of service users. To date, there has been limited research into conceptualizations of mental health care quality among services users diagnosed with bipolar disorder or psychosis. To investigate service user perspectives on quality of care, we conducted six focus groups ( N = 29) with inpatients and outpatients of an independent Irish mental health service. We undertook an inductive thematic analysis of the data. Participants identified proactive staff, meaningful and warm staff–patient interactions, and safety and sociability in the inpatient environment as components of good quality mental health care. Participants also discussed how the implementation of best practice guidelines does not necessarily improve quality of care from the service user perspective. This and similar qualitative research should be used to inform service development and the creation of evaluation instruments compatible with the recovery model.